Intervention in a case of test anxiety, non adaptive perfectionism and procrastination - Furlán, Luis Alberto (2023)
Introduction: the difficulties to regulate emotions in evaluative settings, appear as high levels of anxiety towards tests and avoidance behaviors. Perfectionism traits and procrastinative behaviors, are associated with increasing emotional discomfort across the different steps of the learning/testing cycle. Objective: asses the intervention´s efficacy to improve emotion regulation in evaluative settings. Method: a case study was performed, with the participation of a female universitary law student, who showed high levels of anxiety during oral exams. A six session cognitive behavioral treatment was applied, to diminish test anxiety, non-adaptive aspects of perfectionism and procrastinative behaviors. Quantitative and qualitative data were collected, at the intervention´s beginning and finalization, and six months later. Results: comparative analysis of the pre - post scores, showed a decrease in anxiety and procrastination. Perfectionism scores did not change. The analysis of the qualitative data suggests an increase in sense of control, self confidence, satisfaction with the performance, and more fluid communication during oral exams. Discussion: clinical aspects, functional analysis, and associated symptoms are described, and the results implications are discussed.